PERSIAPAN MAHASISWA JEPANG DALAM MENCARI KERJA - Arifin, Fakhrul; Noor, Redyanto; Trahutami, Sriwahyu (Program Studi Sastra Jepang, Fakultas Ilmu Budaya, Universitas Diponegoro, 2015)
This thesis is research on any process in which students in seeking employment inJapan. The aim of this research is to understand students preparation in seeking theirfirst job.The methods used in this research are library research and descriptivemethod. The theory used in this study is etnosains and ethnometodology.The results showed that, the preparation of students in Japan with job huntinghas been started from two years before they graduated. Many preparation to be doneby students in order to get their desired job. The result shows that systematicemployee recruitment system in Japan make students more discipline and have betterplan for their future.